AB0446 Gastrointestinal bleeding in adult patients with henoch-schönlein purpura. (23rd January 2014) - Nam, E. J.; Kim, N. R.; Kang, J. W.; Jeon, S. W.; Im, C. H.; Kim, S. K.; Park, J. Y.; Jang, Y. J.; Kang, Y. M.
Abstract : Background: Adult Henoch-Schönlein purpura (HSP) has a significantly higher frequency of gastrointestinal (GI) bleeding, compared with childhood HSP. However, the clinical characteristics of GI bleedings in adult HSP are still largely unknown, since the small number of studies performed included case reports and a few case series. Objectives: To investigate clinical manifestations, and endoscopic features of GI lesions in adult HSP patients with GI bleeding. Methods: Twenty-four adult HSP patients, who had evidence of GI bleeding and underwent both upper GI endoscopy and colonoscopy, were included for this study. The controls were twenty-seven adult HSP patients with no evidence of GI bleeding. Results: Patients with GI bleeding showed a significantly higher frequency of palpable purpura on the upper extremities ( p <0.001) and trunk ( p =0.006), and elevated serum CRP ( p <0.001). Multivariate analysis showed that palpable purpura on the upper extremities and elevated serum CRP were independent risk factors for GI bleeding (purpura, OR 79.4, 95% CI 4.2 - 1486.3, p =0.003; CRP, OR 32.3, 95% CI 1.4 - 742.2, p =0.030). Mucosal lesions were found in all 24 patients on the upper GI endoscopy and in 22 patients (91.7%) on the colonoscopy. Furthermore, the concurrent rate of lesions in both upper and lower GI tract was 91.7%. The second portion of duodenum and terminal ileum were the most frequently and severely involved regions in upper and lower GI tract, respectively (2nd portion of duodenum vs. terminal ileum; frequency, 70.8% vs. 75.0%; ulcer, 41.2% vs. 55.6%). In the subgroup analysis with small bowel involvement in 16 patients who underwent both abdominal CT and endoscopic examinations, bowel-wall thickening and mesenteric arterial engorgement on the CT scan were detected in patients with severe lesions including severe petechiae, erosions and ulcers on the endoscopic examinations. In addition, jejunum involvement was observed on the CT scan (n=5, 31.3%), which was associated with more severe lesions on the endoscopic findings. Leukocytoclastic vasculitis (LCV) was also detected in the severe mucosal lesions and significantly correlated with ischemic changes of GI mucosa (upper GI tract, p=0.041; lower GI tract, p <0.001). Most of the mucosal lesions were dramatically improved after one week of glucocorticoid treatment. Two patients with severe multiple ulcers were dead even with treatment of immunosuppressive agents as well as glucocorticoid. Conclusions: This study suggested that both upper and lower GI examinations were necessary for proper evaluation of HSP patients with GI bleeding and provided a good evidence of therapeutic importance for severe mucosal lesions. References: Zhang Y, et al. Gastrointestinal involvement in Henoch-Schonlein purpura. Scand J Gastroenterol 2008;43:1038-1043. Disclosure of Interest: None Declared